(untitled) (Interdisciplinary Research in Education, 2024)
The learning crisis in mathematics is deepening in the context of Nepal. Studies showed that the motivation and engagement of students in learning are decreasing. So, this study was designed to explore the role of feedback in rectifying the mathematics learning crisis. To achieve the objective, classroom-based action research was designed. This action research was conducted in the school located in the Kathmandu district. Five students and their parents were selected as respondents. Interview schedules, observation notes and focus group discussions were used to collect the information and analyze using the thematic analysis method. The result of the study shows feedback strategies such as developing positive learning emotions, providing exemplar assignments, written and oral comments and suggestions, using dialogue and discussion methods in classroom instruction, and providing opportunities for self and peer assessment help to minimize the anxiety of learning mathematics, reduce social media addiction and increase motivation in learning mathematics.